2010
DOI: 10.1158/1535-7163.mct-09-0718
|View full text |Cite
|
Sign up to set email alerts
|

Identification of a Novel Raf-1 Pathway Activator that Inhibits Gastrointestinal Carcinoid Cell Growth

Abstract: Carcinoids are neuroendocrine tumors (NET) that secrete hormones, including serotonin, resulting in the malignant carcinoid syndrome. In addition to the significant morbidity associated with the syndrome, carcinoids are frequently metastatic at diagnosis, and untreated mortality at 5 years exceeds 70%. Surgery is the only curative option, and the need for other therapies is clear. We have previously shown that activation of Raf-1 inhibits carcinoid cell proliferation. We investigated the ability of leflunomide… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
55
0
1

Year Published

2011
2011
2018
2018

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 31 publications
(59 citation statements)
references
References 40 publications
3
55
0
1
Order By: Relevance
“…By contrast, it has been reported that RAF1 activation led to a significant decrease in secretion from medullary thyroid carcinoma cells (decrease of CgA and calcitonin), human pancreatic (BON) and human pulmonary (H727) NET cells (Sippel & Chen 2002, Sippel et al . 2003 a , b , Cook et al . 2010).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…By contrast, it has been reported that RAF1 activation led to a significant decrease in secretion from medullary thyroid carcinoma cells (decrease of CgA and calcitonin), human pancreatic (BON) and human pulmonary (H727) NET cells (Sippel & Chen 2002, Sippel et al . 2003 a , b , Cook et al . 2010).…”
Section: Discussionmentioning
confidence: 99%
“…(2003 b ) found that RAF1 activation did not to influence human pancreatic (BON) NET cell growth, other studies suggested that the RAF1 activator ZM336372 (as well as the drugs leflunomide and teriflunomide – both also associated with RAF1 pathway activation) suppressed the growth of human pulmonary (H727) and human pancreatic (BON) NET cells in vitro ; for leflunomide and teriflunomide, this was also shown in vivo (Van Gompel et al . 2005, Cook et al . 2010).…”
Section: Discussionmentioning
confidence: 99%
“…7 However, the biological function of ASCL1 in laryngeal cancer is not known yet. In order to explore the function of ASCL1 in laryngeal cancer, loss-of-function studies were carried out and found that decreased ASCL1 expression could reduce the growth, migration, and invasion of laryngeal cancer cell lines and induce their apoptosis.…”
Section: Discussionmentioning
confidence: 99%
“…4 It plays an important role in a series of cellular processes such as intracellular transportation and cell division. 5 Some studies indicated that the abnormal expression and function of ASCL1 protein are crucial to the occurrence of human cancers [6][7][8][9][10][11][12] of many kinds, in which increased ASCL1 expression levels have been detected, and silencing ASCL1 expression could suppress the proliferation of both cancer 6,7,10 and neuroendocrine tumor. 5,13,14 And some report that suppression of ASCL1 expression by RNA interference could lead to cellcycle procession as well as cell differentiation and apoptosis and inhibit growth in vitro in an ASCL1 expression-dependent manner.…”
Section: Introductionmentioning
confidence: 99%
“…Although activation of the Ras/Raf/MEK/ERK pathway promotes tumorigenesis in several cancers, it is minimally active or absent in GEP-NETs [39]. Raf-1 activators such as tautomycin and its related compound streptozotocin as well as the anti-rheumatic drug leflunomide have been shown to decrease the expression of NET markers and inhibit in vitro and in vivo carcinoid cell proliferation [40]. Following the demonstration that the Notch 1 signaling pathway acts as a tumor suppressor gene in carcinoid tumors the flavonoid herceptin, a potential Notch 1 activator, has been used as a therapeutic mean.…”
Section: Molecular Classificationmentioning
confidence: 99%